Investigating Heat Development in Shadow Box Façade Systems: A Mockup Test Approach - Singh, Godo Zabur; Arztmann, Daniel; Balderrama, Alvaro (International Scientific Conference on Contemporary Glass Façades)
The popularity of fully glazed facades in office building design has been well-established over the years. One of the techniques used to achieve a seamless outer appearance is the shadow box system, which is composed of two layers of glazing with an air cavity in between. It has gained widespread popularity in markets worldwide due to its potential for creative design and flexibility. However, it is prone to issues such as condensation, contamination, and overheating. This research utilized a mockup test approach to study the issue of overheating in shadow box systems and analyze the main causes of this problem. The findings have significant implications for the design of shadow box systems. The results of the mockup test indicate sun altitude in relation to the geolocation and facade orientation plays a major role in overheating the shadow box. Additionally, careful consideration should be given to the design of ventilation openings to mitigate the overheating issue. This ongoing analysis aims to develop strategies to mitigate the issues found in shadow box systems and future research will involve a comprehensive analysis of various types of shadow box systems.